1993
DOI: 10.1029/92ja01014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the IMF By‐dependent field‐aligned currents in the cleft region based on DE 2 observations

Abstract: The interplanetary magnetic field (IMF) By‐dependent distribution of field‐aligned currents in the cleft region is studied, using the magnetic field and plasma data from 47 passes of Dynamics Explorer (DE) 2. These orbits were chosen on the conditions that cusp/cleft particles are detected and that at the same time the IMF By and Bz components satisfy the criteria |By|≥5 nT and |Bz|≤5 nT during the satellite's crossing of the relevant field‐aligned current region. When By is positive (negative) in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
123
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 46 publications
19
123
1
Order By: Relevance
“…It has been previously documented that the fading phase of PMAFs occurs within the regime of mantle precipitation (Sandholt et al, 1993). Steady-state aspects of the high-latitude dynamo process for the actual IMF orientation (IMF B y > 0) are discussed by, for example, Taguchi et al (1993). Our aurora-convection results are in good agreement with the recent study of Provan et al (2002), showing that the high-latitude pulsed ionospheric flows are observed within the regime of mantle precipitation and can be considered as "fossilized signatures of dayside reconnection, observed as the field lines are being pulled antisunward by the magnetosheath flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously documented that the fading phase of PMAFs occurs within the regime of mantle precipitation (Sandholt et al, 1993). Steady-state aspects of the high-latitude dynamo process for the actual IMF orientation (IMF B y > 0) are discussed by, for example, Taguchi et al (1993). Our aurora-convection results are in good agreement with the recent study of Provan et al (2002), showing that the high-latitude pulsed ionospheric flows are observed within the regime of mantle precipitation and can be considered as "fossilized signatures of dayside reconnection, observed as the field lines are being pulled antisunward by the magnetosheath flow.…”
Section: Discussionmentioning
confidence: 99%
“…One view is that reconnection in such cases can occur where there are antiparallel components in the external magnetosheath magnetic field and the Earth's field (Gonzalez and Mozer, 1974;Cowley, 1981;Sonnerup, 1984;Taguchi et al, 1993;Kawano and Russell, 1997;Siscoe et al, 2001). According to this view, reconnection can take place over large areas of the dayside magnetopause, for example, along a tilted reconnection line traversing the subsolar region and extending to high latitudes in both hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Siscoe and Cummings, 1969;Vasyliunas et al, 1982;Stern, 1984;Taguchi et al, 1993;Siscoe et al, 1991;Farrugia et al, 2003). However, the role of this region as a site of momentum transfer in association with pulsed magnetopause reconnection/FTEs has not been discussed much in the literature, mainly for reasons discussed above.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding magnetic disturbance in the cusp region is estimated approximately as 600 nT. Such a disturbance was observed in the cusp region when B y component of IMF was equal A9 nT (Taguchi et al, 1993). It means that the modelled situation corresponds to the case when B y changes from 0 to A9 nT and back to 0 during an hour.…”
Section: The Modelmentioning
confidence: 92%
“…To investigate the e ects of the disturbed ®eld-aligned current variations in the cusp for IMF B y < 0 we have used the following model input variations of the ®eld-aligned currents based on the data by Rei and Burch (1985), Taguchi et al (1993), Yamauchi et al (1993), and Ohtani et al (1995). We have added the ®eld-aligned current¯owing into (out of) the ionosphere at the Northern (Southern) Hemisphere along the 80°g eomagnetic latitude at the 1130±1400 MLT sector and owing out at the 1000±1130 MLT sector (right top panel in Fig.…”
Section: The Modelmentioning
confidence: 99%